2021
DOI: 10.4069/kjwhn.2021.09.08
|View full text |Cite
|
Sign up to set email alerts
|

Does a nurse-led postpartum self-care program for first-time mothers in Bangladesh improve postpartum fatigue, depressive mood, and maternal functioning?: a non-synchronized quasi-experimental study

Abstract: Purpose: This study aimed to test the efficacy of a nurse-led postpartum self-care (NL-PPSC) intervention at reducing postpartum fatigue (PPF) and depressive mood and promoting maternal functioning among first-time mothers in Bangladesh.Methods: A non-synchronized quasi-experimental design was used. First-time mothers were recruited during postpartum (PP) and assigned to the experimental or control group (34 each). The experimental group attended the NL-PPSC—a 1-day intervention that focused on increasing self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…However, comparing postpartum self-care knowledge mean scores at postpartum six weeks revealed that the intervention group had significantly higher than the control group (t = -6.61, p < 0.001). The result obtained from the current study was consistent with the study done in Indonesia (Khatun et al, 2021). That study used "Nurse-led postpartum self-care (NLPPSC)" intervention which included two sessions of postpartum education and two phone calls in which each lasted three to five minutes for reinforcement at postpartum two and six weeks.…”
Section: Mnci Effect On Postpartum Self-care Knowledgesupporting
confidence: 86%
See 4 more Smart Citations
“…However, comparing postpartum self-care knowledge mean scores at postpartum six weeks revealed that the intervention group had significantly higher than the control group (t = -6.61, p < 0.001). The result obtained from the current study was consistent with the study done in Indonesia (Khatun et al, 2021). That study used "Nurse-led postpartum self-care (NLPPSC)" intervention which included two sessions of postpartum education and two phone calls in which each lasted three to five minutes for reinforcement at postpartum two and six weeks.…”
Section: Mnci Effect On Postpartum Self-care Knowledgesupporting
confidence: 86%
“…The result of RCT conducted in Iran which involved 68 postpartum women showed that four sessions of counseling using the "Skills Training Approach" were effective in increasing the maternal functioning of postpartum women (Chamgurdani et al, 2020) that was alike with the finding of the current study. Finding of the current study was supported by another study done in Indonesia which showed that NLPPSC program was effective in enhancing the maternal functioning of first-time mothers (Khatun et al, 2021). In accordance with the above reviewed studies, maternal functioning of mothers can be promoted by provision of the intervention.…”
Section: Mnci Effect On Maternal Functioningsupporting
confidence: 79%
See 3 more Smart Citations